2017
DOI: 10.5455/njppp.2018.8.0724319072017
|View full text |Cite
|
Sign up to set email alerts
|

A rare case report on Glanzmann thrombasthenia

Abstract: Glanzmann thrombasthenia (GT) is a rare inherited blood clotting disorder characterized by the impaired function of platelets that are essential for proper blood clotting and can lead to prolonged bleeding time. Patient with GT may experience menorrhagia, easy bruising, purpura, epistaxis, and gingival bleeding. Here, we report a case of a young male, who was presented with complaints of malena, epigastric pain, and generalized weakness. Computed tomography and magnetic resonance imaging showed hemoperitoneum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Much of the literature has concluded that GT is diagnosed early, in contrast to this study in which the patient had GT newly diagnosed during surgery at the age of 32. Cherian et al 18 detailed a 28-year-old male with GT who received a late diagnosis. Swathi et al 19 identified an 18-year-old female who had a recent diagnosis of GT but had a history of prolonged bleeding after mild trauma, a propensity to bleed, including purpura in areas of easy bruising, gum bleeding, and prolonged bleeding time after abrasions and insect stings.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the literature has concluded that GT is diagnosed early, in contrast to this study in which the patient had GT newly diagnosed during surgery at the age of 32. Cherian et al 18 detailed a 28-year-old male with GT who received a late diagnosis. Swathi et al 19 identified an 18-year-old female who had a recent diagnosis of GT but had a history of prolonged bleeding after mild trauma, a propensity to bleed, including purpura in areas of easy bruising, gum bleeding, and prolonged bleeding time after abrasions and insect stings.…”
Section: Discussionmentioning
confidence: 99%